Linear programming for the analysis and virtual recreation of historical events: the allocation of the artillery during the Siege of Bilbao in 1874 - Alvaro Rodriguez-Miranda; Patricia Ferreira-Lopes; Gorka Martín-Etxebarria; Jaione Korro Bañuelos (Virtual Archaeology Review)
The current digital technologies development makes it possible to apply new forms of studying historical events considering the geographical point of view. They rely on the location and the relationships among the different elements that took part in them over a recreated space (e.g. relief, roads, rivers); once these elements have been laid out on the virtual space, Geographic Information Systems (GIS) can be used to analyse several factors, such as distances, visibility, connectivity and so on. Nevertheless, the development of the actions was also driven by the aims, needs and beliefs (either wise or misguided) of the people/actors involved in those situations; therefore, some ways of including reasoning would significantly improve the actual recreation and understanding of the episodes. In this sense, “linear programming” is a very versatile tool for system modelling and optimization that is broadly used in many fields (e.g. industry, transports, agriculture, etc.). Likewise, this technique can also be applied to past scenarios to simulate dynamics and cross-check sources. In this text, two models regarding the distribution and the allocation of supplies during the siege of Bilbao, in the framework of the Third Carlist War (1872-1876), from both parties —beleaguerer and besieged— were established based on the war front textual reports. In these models, the scenario is recreated through the system variables (which define the alternatives that can be or could have been taken) and the constraints (which limit the range of action); moreover, the actors’ goals that guided the course of events are defined by the objective. Despite the simplification in the modelling, the results show very interesting hints about the dynamics involved during the processes and are able to highlight some critical issues that significantly conditioned the final results. Besides, the modelling process itself proved to be an opportunity for collaboration between historians and computer scientists.